Family cluster of three recovered cases of pneumonia due to severe acute respiratory syndrome coronavirus 2 infection. Issue 5 (4th May 2020) - Xiong, Yong; Song, Shihui; Ye, Guangming; Wang, Xinghuan
Abstract : The coronavirus disease (COVID-19) outbreak caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first reported in Wuhan, China, in late 2019 and has affected more than 1 270 000 people worldwide. The numbers of reported cases continue to rise and threaten global health. Transmissions among family members are frequently observed, although the route of transmission is partially known. Here we report three cases of SARS-CoV-2 infection within one family. Sequencing of the S gene of the viral genome showed 100% identity among samples, suggesting that the same strain caused the infection. Following treatment with oseltamivir and short-term methylprednisolone combined with symptomatic management, all three patients recovered within 3 weeks, as evidenced by the disappearance of their symptoms, clearance of pulmonary infiltrates and consecutive negative molecular diagnostic test findings. Our observations suggest the importance of preventing family transmission and the efficacy of current integrated treatment for mild/moderate pneumonia in COVID-19 cases.